2016
DOI: 10.4293/jsls.2016.00078
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Pressure Changes With Positioning During Laparoscopy

Abstract: Background and Objectives:Pneumoperitoneum during laparoscopy can produce changes in intraocular pressure (IOP) that may be influenced by several factors. In this study, we investigated changes in IOP during laparoscopy with different positioning.Methods:We recruited adult patients without eye disease scheduled to undergo laparoscopic operation requiring a reverse Trendelenburg tilt (rTr; group A; n = 20) or Trendelenburg tilt (Tr; Group B; n = 20). IOP was measured at 7 time points (T1–T7). All procedures wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…3 Additionally, there is an increase in IOP and vitreous pressure from increased venous pressure. 4 , 5 This may be compensated for by raising the height of the infusion bottle. 6 Similarly, every patient presenting with spinal deformities will have curvature of the spine to varying degrees.…”
Section: Discussionmentioning
confidence: 99%
“…3 Additionally, there is an increase in IOP and vitreous pressure from increased venous pressure. 4 , 5 This may be compensated for by raising the height of the infusion bottle. 6 Similarly, every patient presenting with spinal deformities will have curvature of the spine to varying degrees.…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative visual disturbance or loss has been reported as an uncommon side effect after such a procedure. 42 , 43 , 44 , 45 , 46 This presumably results from the transmission of IAP along the spine into the skull base EDNAC segments and then through into the orbit, causing increased intraocular pressure (IOP). Adisa et al 45 reported that the resultant intraocular venous congestion in the orbital EDNAC segment can manifest as perioperative visual impairment via ischemic optic neuropathy or retinal vascular occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon of an elevated IOP can be further exacerbated by patient positioning during operations, particularly in the steep Trendelenburg and prone jackknife positions where the effects of gravity, in tandem with an increased IAP, can further elevate ICP and IOP. 44,45,[47][48][49] Such a prolonged head-down orientation during surgical procedures should best be avoided for fragile patients (e.g., those with a diagnosis of coronavirus disease 2019). A number of recent reports have emphasized the use of the prone position for surgery in this patient group as this position will minimally alter IAP and IOP.…”
Section: Pressure Transductionmentioning
confidence: 99%
“…The results describe a significant IOP increase in the Trendelenburg position after pneumoperitoneum introduction, which returned to baseline values in the supine position after pneumoperitoneum evacuation. In their study on adult humans, Adisa et al (2016) observed a mild increase in IOP after pneumoperitoneum induction, with a mean difference of +2.85 mmHg in the reverse Trendelenburg and +0.40 mmHg in the Trendelenburg group. Also, Grosso et al (2013) found that standard pneumoperitoneum pressures (≤ 14 mmHg) led to mild and reversible IOP increases.…”
Section: Parametermentioning
confidence: 94%